CHARACTER EDUCATION IN BANJARAN BIMA PLAY AND ITS IMPLICATION IN EDUCATION - Dwijonagoro, Suwarna; Meilawati, Avi; Nurhidayati, Nurhidayati; Wulan, Sri Hertanti (LPPM Universitas Negeri Yogyakarta, 2019)
Character education is very essential. Good character brings peace, happiness and peace of mind, both personally and socially, even for the nation. Character education reflection is shown in many puppet shows. Wayang as a spectacle and guidance. Wayang as a spectacle is for entertainment, while as a guidance is a vehicle for character education. Which is indeed full of character education. The data source of this research was